Efektivitas Program Pemberdayaan Ekonomi Syariah Melalui UMKM di Kabupaten Pringsewu - Anasya, Mirza; Astuti, Sri Yuli; Mardian, Husni (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
This research discusses the empowerment of UMKM in the Pringsewu Regency with a focus on the application of Sharia economic principles. UMKM has an important role in economic development in Indonesia, accounting for around 61.07% of the Gross Domestic Product (GDP) and accommodating up to 97% of the labor force. To maximize the role of UMKM in driving economic growth, Sharia-based empowerment efforts are one of the solutions applied. This research uses qualitative research by providing interviews and training to research subjects as data collection techniques. In addition, this study also conducted in-depth observations of research subjects and provided a socialization approach that was given to add insight and knowledge for UMKM actors in the Pringsewu district. The data was analyzed through SWOT analysis to identify suitable strategies for developing Sharia-based UMKM. From the results of the research conducted, it is stated that the drivers of UMKM in the Pringsewu Regency have implemented Sharia economic principles properly and according to the recommendations in Islam. Apart from that, UMKM drivers in the Pringsewu district are motivated and encouraged by several factors. One of them is family and social environmental factors that help motivate individuals to continue running Sharia-based businesses.